Clinical decision support improves quality of care in patients with ulcerative colitis. Issue 8 (7th March 2019) - Jackson, Belinda; Begun, Jake; Gray, Kathleen; Churilov, Leonid; Liew, Danny; Knowles, Simon; De Cruz, Peter
Summary: Background: Decision support tools may facilitate shared decision‐making and improve quality of care. Aim: To assess the effectiveness of a decision support tool on improving quality of care in ulcerative colitis. Methods: A prospective quality of care intervention was conducted at two Australian hospitals comparing out‐patient–based ulcerative colitis care with, and without, a tablet‐based decision support tool. This included questions on disease activity management; psychological well‐being; and preventive care, with 13 process indicators relevant to each domain. Participants included adult out‐patients with mild‐to‐moderate ulcerative colitis and their clinicians who were divided into two cohorts. The first cohort were followed up immediately after their clinical review to check whether their clinician had discussed the 13 process indicators during the consultation. The second cohort of patients used the decision support tool immediately prior to their consultation which then generated a suggested management plan for the patient and clinician to discuss during the consultation. Management between the 2 cohorts was compared to assess the effectiveness of the decision support tool in improving the primary outcome, defined as the proportion of quality process indicators used for ulcerative colitis care, with and without the decision support tool. Results: Thirteen physicians and 100 patients participated. Fifty patients were managed without the decision support tool using standard care (median age 40; 44% male), and 50 patients used the decision support tool (median age 40; 46% male) over a 20‐week period. Increase in the median use of process indicators overall was observed following use of the decision support tool (27% vs 100%; P  < 0.001). Improvements were seen in psychological well‐being management (30% vs 100%; P  < 0.001), preventive care (16% vs 100%; P  < 0.001) and process indicators related to disease activity management (50% vs 100%; P  < 0.001). The decision support tool was found to be usable and acceptable. Shared decision‐making was greater in the post‐intervention group (mean decision conflict score of 18.0 vs 33.5; P  = 0.002). Conclusions: The decision support tool substantially improved the quality of the delivery of care. Decision support tools have the potential to minimise errors of omission via a standardised approach to care.